2016
DOI: 10.5858/arpa.2016-0042-ra
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes Tumor of the Breast: Histopathologic Features, Differential Diagnosis, and Molecular/Genetic Updates

Abstract: Context.-Phyllodes tumor (PT) of the breast is a rare fibroepithelial neoplasm with risks of local recurrence and uncommon metastases. The classification proposed by the World Health Organization for PTs into benign, borderline, and malignant is based on a combination of several histologic features. The differential diagnosis between PT and fibroadenoma and the histologic grading of PT remain challenging. In addition, the molecular pathogenesis of PT is largely unknown.Objective.-To provide an updated overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
237
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(260 citation statements)
references
References 53 publications
(62 reference statements)
4
237
0
19
Order By: Relevance
“…Studies have shown that p53, Ki67, CD117, EGFR, p16 and VEGF are associated with histological grades. 29 The results indicate that the lowest expression is correlated with benign phyllodes tumours, meanwhile the highest is in malignant type. In fact, they may be valuable in differentiating fibroadenomas from phyllodes tumors and even to separate between grades of phyllodes tumours.…”
Section: Diagnosismentioning
confidence: 97%
“…Studies have shown that p53, Ki67, CD117, EGFR, p16 and VEGF are associated with histological grades. 29 The results indicate that the lowest expression is correlated with benign phyllodes tumours, meanwhile the highest is in malignant type. In fact, they may be valuable in differentiating fibroadenomas from phyllodes tumors and even to separate between grades of phyllodes tumours.…”
Section: Diagnosismentioning
confidence: 97%
“…As patients with metastatic PTs may not respond well to standard chemotherapy, death often ensues [4]. As many as 15 studies summarized in Table 1 describe a 100.0% mortality rate amongst patients with metastatic PTs.…”
Section: Prognosis Of Patients With Metastasis In Ptmentioning
confidence: 99%
“…The local recurrence rate is around 20% in benign PT and is up to 25% in borderline PT. In malignant PT, the recurrence rate may as high as 40% and distant metastases may occur in 9% to 27% of cases 4 . The bilateral synchronous or metachronous representation of breast PTs is very rare.…”
Section: Figure 1 Positron Emission Tomography-computed Tomography (mentioning
confidence: 99%
“…This classification is based on histologic features that include stromal hypercellularity, cellular pleomorphism, mitosis (per 10 HPF), tumor margin and stromal pattern 1 . Phyllodes tumors are benign in 60% -75% of cases, borderline in 12% -26% and malignant in 10% -15% 4 . A number of reports described bilateral breast PTs which is an uncommon presentation of this relatively rare tumor [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%